Ethnic consciousness and identity among Lithuanian-American/Canadian adolescents - Norvilas, Algis (Psichologija, 1999)
Eighty-two Lithuanian-American/Canadian adolescents responded in writing to eleven questions regarding their Lithuanian and American ethnic consciousness and identity. A phenomenological analysis of their written responses revealed a complex ethnic-identity-structure. The adolescents saw themselves as both Lithuanian and American. Their Lithuanian identity was based on three external components: descent (ancestry), ethnic involvement, and language, and the internal feeling of pride and satisfaction and sense of belonging and purpose. They regarded their Lithuanian identities as essential aspects of their personality, without which they would have felt empty and different. Their American identity consisted of three components: awareness of birthright, social involvement, and emotional ties. The relationship between the two identities was a dynamic one, each coming to the fore or receding as a result of context: e. g., an adolescent might feel more Lithuanian amongst fellow Lithuanians. Interestingly enough, there was little evidence of conflict between the two identities. The main complaint the participants expressed was that at times they felt overextended, that there was too much to do.